(untitled) (Global Journal of Medical Research, 2017)
The identification of Kayser-Fleischer (KF) ring remains the most important clinical sign for the diagnosis of Wilson disease (WD). Slit lamp biomicroscope (SL) examination by a skilled observer is still the preferred method of evaluating KF ring. Anterior segment optical coherence tomography (AS-OCT) is an alternative method of evaluating KF ring in WD. Hyper-reflective layer in the corneal periphery at the level of Descemet membrane (DM) is the characteristic appearance of KF ring on AS-OCT. In a suspected case of WD, features of KF ring on AS-OCT may alert the clinician to do a careful SL examination to look for early KF ring. AS-OCT has been found useful in measuring the length of KF ring with ease even in patients with severe rigidity and children. AS-OCT can measure the length of KF ring better compared to SL in patients with limbal pathology. Early detection of increased corneal copper even before KF rings appear is a potential area for future research.